Re-examining the Noncitizen Within the Frame of Citizenship: Reflections and Considerations from the Indian experience: Reexaminando al no-ciudadano dentro del marco de la ciudadanía: reflexiones y consideraciones desde la experiencia india - Chowdhory, Nasreen (Araucaria, 2025)
Various scholars have remarked that citizenship has evolved from a statist notion to denationalised, post-nationalised, disaggregated, de-territorialised and cosmopolitanised notion of rights[1]. Citizenship is a legal status based on nationality by the nation state. The status accorded by state denotes legal and social rights in society. Citizenship indicates a territorial and bounded notion of rights based on membership. But the post globalisation debates suggest an expansion and decoupling of nationality driven rights to a more holistic understanding of rights-based discourse accommodating the question of noncitizens. The paper seeks to examine the noncitizen as a category to understand whether it can exist outside the binary of citizenship while engaging with the Citizenship Amendment Act, 2019. The paper traces the journey of a noncitizen to a citizen, while attesting citizenship to be a territorialised set of rights within the nation state. [1] Nasreen Chowdhory, Shamna Thacham Poyil, and Meghna Kajla. “The Idea of Protection: Norms and Practice of Refugee Management in India.” Refugee Watch 53 (2019): 36–54.